DETERMINATION OF OZONE CONCENTRATION AND ITS EFFECT ON DEGRADATION OF MATERIALS - Romana FRIEDRICHOVÁ; Jan KARL; Milan RŮŽIČKA; Anna VYSKOČILOVÁ; Marek MARTINEC; Martin VESELÝ; Jan ŠKUBNÍK; Vladimíra SVOBODOVÁ PAVLÍČKOVÁ; Silvie RIMPELOVÁ; Martin KUCHAŘ (Transactions of the VŠB: Technical University of Ostrava, Safety Engineering Series, 2022)
The ongoing Covid-19 pandemics showed the need for the effective decontamination of environment and surfaces. One of the options could be the use of gas ozone. Ozone has been well known for its disinfection properties, which were in the past used to decontaminate water. In this article, we present a development of an easy-made and ready-to-use portable detector of ozone, which could be used to easily detect ozone in the environment. In addition, we studied degradation impact of ozone on different materials, which normally occur in households or at working places. Ozone is well detectable and does not cause any damage to materials at concentrations needed for decontamination of the environment.